Pemberdayaan Kelompok Tani Hutan Malilu Sipakainga Berbasis Pengembangan Usaha Kemiri di Desa Alu, Sulawesi Barat - Rini Pratiwi; Andi Irmayanti Idris; Ulfa Adzkia (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
This community service activity aims to empower the Malilu Sipakainga Forest Farmers Group (KTH) in Alu Village, Alu District, Polewali Mandar Regency, West Sulawesi Province, through the development of candlenut businesses as a local potential from the forestry sector. The activity is based on capacity building in packaging, logo design, and digital marketing. The implementation method was carried out through participatory training with members, including material delivery, hands-on practice, and intensive mentoring. The results of the activity show that participants are able to produce more attractive packaging designs for peeled candlenut and powder products, design logos as product identities, and create social media accounts to market products more widely. The impact of this activity not only increases knowledge and technical skills but also fosters self-confidence, entrepreneurial spirit, and cooperation in business. From an economic perspective, the activity has proven to increase the added value of products through the implementation of several innovations ranging from packaging, logos, and digital marketing. The conclusion of this activity is that strengthening the capacity of KTH Malilu Sipakainga members through the innovations implemented can contribute to increasing the competitiveness and welfare of the local community. Furthermore, intensive mentoring and support for business facilities from the local government, as well as multi-stakeholder collaboration, are needed to ensure that this community-based candlenut business can continue to grow.